2018
DOI: 10.1177/1039856218781018
|View full text |Cite
|
Sign up to set email alerts
|

Building workforce capacity in Australia and New Zealand: a profile of psychiatrists with an interest in intellectual and developmental disability mental health

Abstract: While some elements of the IDDMH workforce profile suggest this workforce is tailored to the needs of the population, the potential shortage of IDDMH psychiatrists highlights the need for the development of a specific training programme and pathway in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…The characteristics of the sample (including age, practice location, sector, work hours, retirement plans and outreach work) were consistent with results from the RANZCP workforce survey for those working in IDD (see Cvejic et al 2018)4 for a comparison of the IDD versus broader psychiatry workforce). While Cvejic et al (2018)4 found no significant difference in the average age of IDD versus other psychiatrists overall, the smaller proportion of psychiatrists aged 30-39 years may be due in part to the shortage of public sector positions, lack of clear career pathways and absence of subspecialty training in this area. The shortage of IDD psychiatrists in locations such as Tasmania demonstrates the importance of outreach work.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The characteristics of the sample (including age, practice location, sector, work hours, retirement plans and outreach work) were consistent with results from the RANZCP workforce survey for those working in IDD (see Cvejic et al 2018)4 for a comparison of the IDD versus broader psychiatry workforce). While Cvejic et al (2018)4 found no significant difference in the average age of IDD versus other psychiatrists overall, the smaller proportion of psychiatrists aged 30-39 years may be due in part to the shortage of public sector positions, lack of clear career pathways and absence of subspecialty training in this area. The shortage of IDD psychiatrists in locations such as Tasmania demonstrates the importance of outreach work.…”
supporting
confidence: 63%
“…However, the profile of respondents is largely consistent with the characteristics of the larger sample in Cvejic et al (2018). 4 Secondly, data on the pathways psychiatrists took to work in IDDMH was outside the scope of this report. However, this data is essential to identifying avenues for enhancing workforce capacity and is thus detailed in Eagelson et al (2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Davies et al 9 reported that there was reasonable coverage of IDD psychiatrists in metropolitan areas (supporting findings from Cvejic et al 10 ), but the majority were working limited hours in IDD. The workforce is therefore unlikely to meet future needs without the development of suitable training pathways.…”
mentioning
confidence: 80%
“…8,15 Our findings indicate that psychiatrists in Australia and New Zealand strongly support subspecialty training in IDDMH and potentially have the training capacity to implement this. Given projected IDDMH workforce shortages, 10 there is an urgent need to act on calls for subspecialty training in IDDMH to improve equitable access to mental health care for people with IDD 1 and to meet the aims of national mental health policy. 4 This would help ensure that people with IDD receive quality mental health care across mainstream services, and that there are sufficient psychiatrists to provide specialist services to those with complex needs.…”
Section: Discussionmentioning
confidence: 99%